Bluey. Season 3 [videorecording (DVD)] - Brumm, Joe (BBC, 2024)
The multi-award-winning pre-school animation, loved by children and their families around the world, returns for its highly anticipated third series. Bluey and her little sister Bingo love coming up with hilarious, elaborate games based on their interpretation of the world around them. They enjoy nothing more than roping Mum Chilli and Dad Bandit and all their family, friends, and neighbors into their daily fun. Series 3 brings more of the authentic and relatable stories around everyday life that audiences adore. It features fan favorites such as Muffin, Socks, and the Grannies, and introduces some new friends too.